Mineral accumulation in vegetative and reproductive tissues during seed development in Medicago truncatula - Garcia, Christina B.; Grusak, Michael A. (Frontiers in Plant Science, 2015)
Enhancing nutrient density in legume seeds is one of several strategies being explored to improve the nutritional quality of the food supply. In order to develop crop varieties with increased seed mineral concentration, a more detailed understanding of mineral translocation within the plant is required. By studying mineral accumulation in different organs within genetically diverse members of the same species, it may be possible to identify variable traits that modulate seed mineral concentration. We utilized two ecotypes (A17 and DZA315.16) of the model legume, Medicago truncatula, to study dry mass and mineral accumulation in the leaves, pod walls, and seeds during reproductive development. The pod wall dry mass was significantly different between the two ecotypes beginning at 12 days after pollination, whereas there was no significant difference in the average dry mass of individual seeds between the two ecotypes at any time point. There were also no significant differences in leaf dry mass between ecotypes; however, we observed expansion of A17 leaves during the first 21 days of pod development, while DZA315.16 leaves did not display a significant increase in leaf area. Mineral profiling of the leaves, pod walls, and seeds highlighted differences in accumulation patterns among minerals within each tissue as well as genotypic differences with respect to individual minerals. Because there were differences in the average seed number per pod, the total seed mineral content per pod was generally higher in A17 than DZA315.16. In addition, mineral partitioning to the seeds tended to be higher in A17 pods. These data revealed that mineral retention within leaves and/or pod walls might attenuate mineral accumulation within the seeds. As a result, strategies to increase seed mineral content should include approaches that will enhance export from these tissues.